Morphological Variations among Different Accessions of Jatropha curcas L. - Tandel, M. B.; Kukadia, M. U.; Parmar, M. R.; Patel, N. K. (Indian Forester, 2016)
Fifteen (15) accessions of Jatropha curcas viz., NAUJ-6, NAUJ-7, SKNJ-7, SKNJ-11, TFRI-1, TFRI-2, PKVJ-HW-1, PKVJ-SJ-1, MPC-CH-B, MPC-UD-J, MPC-UD-K, PANT-J-SEL-1, PANT-J-SEL-2, PAUJ-1 and CCSH-1 were assessed. The different morphological parameters were significantly influenced by different accessions under study during the two years and also in pooled analysis. The traits like plant height, number of branches per plant, number of inflorescence per plant, number of fruits per plant and seed yield per plant were noted observed significantly maximum in the accession MPC-CH-B; collar diameter in the accession PAUJ-1; leaf area in the accession PANT-J-SEL-2; angle of branching in the accession TFRI-2 and 100 seed weight in the accession TFRI-1. Whereas, earlier flowering was noted in the accessions MPC-UD-J. Seed oil content varied from 24.307 to 33.326 %. It was significantly higher in accession TFRI-1 while it was minimum in accession CCSH-1. Correlation matrix of seed yield with various morphological parameters indicated that seed yield was significantly and positively correlated with number of inflorescence per plant, number of fruits per plant, plant height, 100 seed weight and number of branches per plant.